2007
DOI: 10.1254/jphs.fp0070865
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Is a Key Organella in Bradykinin-Triggered ATP Release From Cultured Smooth Muscle Cells

Abstract: Abstract. ATP has broad functions as an autocrine / paracrine molecule. The mode of ATP release and its intracellular source, however, are little understood. Here we show that bradykinin via B 2 -receptor stimulation induces the extracellular release of ATP via the inositol 1,4,5-trisphosphate [Ins(1,4,5)P 3 ]-signaling pathway in cultured taenia coli smooth muscle cells. It was found that bradykinin also increased the production of Ins(1,4,5)P 3 and 2-APB-inhibitable [CaThe evoked release of ATP was suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…3,108 Under physiological conditions, cytosolic ATP can be released via transmembrane transport in response to receptor activation in both vascular smooth muscle cells and endothelial cells. 96,98,68,123 In most neurons, ATP is stored in vesicles with neurotransmitters and coreleased. 16,40 Under experimental conditions various environmental stressors, such as a mechanical stress, have been used as stimuli to release ATP.…”
Section: +mentioning
confidence: 99%
“…3,108 Under physiological conditions, cytosolic ATP can be released via transmembrane transport in response to receptor activation in both vascular smooth muscle cells and endothelial cells. 96,98,68,123 In most neurons, ATP is stored in vesicles with neurotransmitters and coreleased. 16,40 Under experimental conditions various environmental stressors, such as a mechanical stress, have been used as stimuli to release ATP.…”
Section: +mentioning
confidence: 99%
“…Searches for potential mechanosensitive systems revealed that very modest shear stress, extracellular fluid movement, and cell volume modulation led to the release of ATP, UTP, and other nucleotides from almost all cell types studied so far, including VSMC and endothelial cells [13][14][15]. It was also documented that activation of ligandgated P2X receptor cation channels and G protein-coupled P2Y receptors with released nucleotides contributed to the autocrine regulation of blood vessel tone and remodeling [16,17].…”
mentioning
confidence: 99%
“…We have reported previously that intracellular Ca 2+ levels in endothelial cells are increased by ATP derived from cancer cells 2 and several studies have shown that ATP is released from various types of cells, including cancer cells 3–7 . Several investigators have examined the mechanisms of ATP release, among which Cl − channels comprise one candidate route.…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported that intracellular Ca 2+ levels in human umbilical vein endothelial cells are increased in the presence of coexisting human fibrosarcoma (HT‐1080) cells and that this response is caused by ATP derived from the cancer cells 2 . Accumulating reports indicate that various cell types can release ATP 3–7 . For example, in HTC rat hepatoma cells, swelling induced by hypotonic exposure increases the extracellular ATP concentration 3 .…”
Section: Introductionmentioning
confidence: 93%